Impacts of atmospheric particulate matter pollution on environmental biogeochemistry of trace metals in soil-plant system: A review - Luo, Xiaosan; Bing, Haijian; Luo, Zhuanxi; Wang, Yujun; Jin, Ling (Environmental pollution (1987), 2019)
Atmospheric particulate matter (PM) pollution and soil trace metal (TM) contamination are binary environmental issues harming ecosystems and human health, especially in the developing China with rapid urbanization and industrialization. Since PMs contain TMs, the air-soil nexus should be investigated synthetically. Although the PMs and airborne TMs are mainly emitted from urban or industrial areas, they can reach the rural and remote mountain areas owing to the ability of long-range transport. After dry or wet deposition, they will participate in the terrestrial biogeochemical cycles of TMs in various soil-plant systems, including urban soil-greening trees, agricultural soil-food crops, and mountain soil-natural forest systems. Besides the well-known root uptake, the pathway of leaf deposition and foliar absorption contribute significantly to the plant TM accumulation. Moreover, the aerosols can also exert climatic effects by absorption and scattering of solar radiation and by the cloud condensation nuclei activity, thereby indirectly impact plant growth and probably crop TM accumulation through photosynthesis, and then threat health. In particular, this systematic review summarizes the interactions of PMs-TMs in soil-plant systems including the deposition, transfer, accumulation, toxicity, and mechanisms among them. Finally, current knowledge gaps and prospective are proposed for future research agendas. These analyses would be conducive to improving urban air quality and managing the agricultural and ecological risks of airborne metals. [Display omitted] •Atmospheric dry and wet deposition input metals into soil-plant system.•Urban tree leaves remove atmospheric particulates and trace metals.•Foliar absorption of some airborne metals more than crop root uptake.•Aerosols impact solar radiation for plant photosynthesis and crop production.•Long-range atmospheric transport of trace metals impact mountain ecosystems.